(untitled) (Annals of Medical Research, 2026)
Aim: Depressive disorders affect around 10% of pregnant women. Antidepressant use during pregnancy is important for maternal and fetal health. Although studies link antidepressants to risks of spontaneous abortion, preterm labor, and postpartum hemorrhage, their direct effects on the myometrium remain unclear. This study investigated the effects of sertraline and escitalopram on spontaneous and oxytocin-induced contractions in rat myometrial tissue. Materials and Methods: 6 pregnant and 14 nonpregnant female Sprague-Dawley rats were used in the study. Myometrial strips measuring 1x0.2x0.2 centimeters were obtained from rats. Female rats were decapitated on day 18-20 of gestation. In oxytocin-induced and spontaneous contractions, sertraline and escitalopram were added cumulatively at concentrations of 1 μM, 3 μM and 10 μM in pregnant and nonpregnant rat groups and AUC (Area Under the Curve), frequency and amplitude values were recorded. Results: Regression analysis demonstrated a significant dose-dependent decrease in AUC (particularly under oxytocin). Holm-Bonferroni adjusted Wilcoxon tests confirmed that sertraline reduced AUC during oxytocin-induced contractions in both nonpregnant and pregnant strips, while escitalopram showed no significant effects on AUC, amplitude, or frequency. Conclusion: In vitro, AUC decreased dose-dependently—particularly with sertraline during oxytocin-induced contractions—while the effects of escitalopram were inconsistent. These results may support cautious use of the lowest effective dose in pregnancy and motivate further translational work.